An evaluation of the prevalence, cause and risk factors associated with leucorrhoea in reproductive age group women - Arthy, A. Priya; Sen, Sangeeta; Kumar, A. Ganesh; Rajaram, R.; Archunan, G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The community based study was carried out in women of reproductive age group with a specific aim to evaluate the prevalence and risk factors of leucorrhoea. Methods: In this investigation, a total of 191 women who presented with gynaecological complaint of white discharge and seeking medical assistance was taken as a study sample for PAP smear. The basic details like socio demographic, past obstetric history and menstrual history were included prior to the smear study. Results: High prevalence of vaginal discharge was observed in the age group of 30-39, those who had two parity, previous obstetric history of normal vaginal delivery and usage of Copper T as a method of contraception. The binary logistics model explains the risk factors levels of abnormal vaginal discharge with 95% confident interval. Based on the data analysed, the age group of 30-39 and 40-49 are more likely to have a risk of 3.22 and 2.68 folds respectively. Likewise, the participants with the history of diabetes had a 2.08 folds increased risk of leucorrhoea rather than other complications and 2.21 folds of risk to those who used barrier methods like condom as a contraceptive method. Conclusions: The results concluded that the occurrence of vaginal discharge in women is age dependent and the most common risk factors for causing the vaginal discharge in the reproductive age group i.e. 30-49 years of age, are previous normal vaginal delivery, diabetes and usage of contraceptive methods like intra uterine contraceptive device and barrier methods.